Mixed-method development and feasibility analysis of CETING mobile application for digital stunting monitoring - Affi Zakiyya; Elma Marsita; Ratna Indah Kartika Sari (Universitas Aisyiyah Yogyakarta, 2026)
Independent monitoring of toddler growth is a crucial step in stunting prevention; however, conventional methods like the KIA handbook are often perceived as impractical by modern parents. This study aims to develop and evaluate the feasibility of growth monitoring features within the CETING application as a digital solution for early stunting detection. An R&D approach was employed, involving validation by material and media experts, followed by a small-group trial with 15 mothers of toddlers. Data were gathered through Likert-scale questionnaires and in-depth interviews to gain qualitative perspectives. Expert validation indicated high feasibility, with scores of 90.00% from material experts and 85.00% from media experts. The user trial yielded an overall feasibility score of 89.38% (Very Feasible), with